Practicality of Integrated Thematic Teaching Materials Based on Project Based Learning (PjBL) in Class 4 Elementary School - Muniroh Siregar; Reinita Reinita (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2022)
Teaching Materials are one of the learning resources used to support educators and students in teaching and learning activities. The purpose of this study is to develop integrated thematic teaching materials based on project-based learning (PjBl) in 4th grade elementary school. The type of survey conducted is a development survey (R & D) using a 4D development model (definition, design, development, diffusion). The subjects of this study were 15 fourth graders of SDN015 Simangambat. Research results on the development of developed thematic teaching materials, the results of the field test of the teacher's answer questionnaire that achieved 91.66% of the results, and the result of the field test of the student's answer questionnaire, the result was 94.66%..Thus, it can be said that the integrated thematic learning teaching materials in fourth grade elementary school have been used practically.